2021
DOI: 10.3390/cancers13164195
|View full text |Cite
|
Sign up to set email alerts
|

Germline PALB2 Mutation in High-Risk Chinese Breast and/or Ovarian Cancer Patients

Abstract: The prevalence of the PALB2 mutation in breast cancer varies across different ethnic groups; hence, it is of intense interest to evaluate the cancer risk and clinical association of the PALB2 mutation in Chinese breast and/or ovarian cancer patients. We performed sequencing with a 6-gene test panel (BRCA1, BRCA2, TP53, PTEN, PALB2, and CDH1) to identify the prevalence of the PALB2 germline mutation among 2631 patients with breast and/or ovarian cancer. In this cohort, 39 mutations were identified with 24 types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Furthermore, PALB2 mutations have been associated with an increased risk of breast cancer similar to BRCA2 mutations 41 . Therefore, the inclusion of the PALB2 in genetic testing panels for high-risk breast and ovarian cancer patients is crucial, as demonstrated in a study on Chinese patients 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, PALB2 mutations have been associated with an increased risk of breast cancer similar to BRCA2 mutations 41 . Therefore, the inclusion of the PALB2 in genetic testing panels for high-risk breast and ovarian cancer patients is crucial, as demonstrated in a study on Chinese patients 42 .…”
Section: Discussionmentioning
confidence: 99%
“…These authors showed that BRCA1 PVs were higher in Ashkenazi Jewish women and Hispanic women compared to NHW, checkpoint kinase 2 (CHEK2) PVs were statistically significantly lower in Black and Asian women, BRCA1associated RING domain 1 (BARD1) PVs were associated with high BCR in Black, Hispanic, and Asian women, and ataxia-telangiectasia mutated (ATM) PVs were associated with increased BCR among all races and ethnicities except Asian people, whereas CHEK2 and BRIP1 PVs were associated with increased BCR among NHW and Hispanic women [48]. Moreover, Kwong et al (2021) showed that the prevalence of the partner and localizer of the BRCA2 (PALB2) mutation in BC also varies across different ethnic groups [49]. Germline PVs of the PALB2 tumor suppressor gene, which binds to and co-localizes with BRCA2 in the DNA repair pathway [50], are associated with an increased BCR, more aggressive phenotypes, particularly the TNBC subtype, and higher mortality [51].…”
Section: Genetics/genomics Of Breast Cancer Disparitiesmentioning
confidence: 97%
“…Monoallelic mutations of PALB2 predispose to cancers development and have been linked to hereditary breast and ovarian cancer (HBOC) syndrome [28,29]. Breast Cancer Association Consortium recently classified these mutations in the high-risk category for its protein-truncating variants [24 & ]; the estimated risk to age 80 years has been quoted at 53% for female BC and 5% for ovarian cancer [30].…”
Section: Moderate Penetrance Breast Cancer-susceptibility Genesmentioning
confidence: 99%